The Problem of Punishment - Boonin, David (Cambridge University Press, 2013)
In this book, David Boonin examines the problem of punishment, particularly the problem of explaining why it is morally permissible for the state to treat those who break the law differently from those who do not. Boonin argues that there is no satisfactory solution to this problem and that the practice of legal punishment should therefore be abolished. Providing a detailed account of the nature of punishment and the problems that it generates, he offers a comprehensive and critical survey of the various solutions that have been offered to the problem and concludes by considering victim restitution as an alternative to punishment. Written in a clear and accessible style, The Problem of Punishment will be of interest both to anyone looking for a critical introduction to the subject and to anyone who is already familiar with it.